If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 8d = 10d Solving 10 + 8d = 10d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-10d' to each side of the equation. 10 + 8d + -10d = 10d + -10d Combine like terms: 8d + -10d = -2d 10 + -2d = 10d + -10d Combine like terms: 10d + -10d = 0 10 + -2d = 0 Add '-10' to each side of the equation. 10 + -10 + -2d = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2d = 0 + -10 -2d = 0 + -10 Combine like terms: 0 + -10 = -10 -2d = -10 Divide each side by '-2'. d = 5 Simplifying d = 5
| 3(10+2y)7= | | -10+7h-5=10h+6 | | 3sin^2x-sinx+1=0 | | 72/x=3.6/0.015 | | 2x=150+15x | | -8+7m=5m | | 72÷x=3.6/0.015 | | 72/x=3.6÷0.015 | | 2k^2-12=0 | | 5b-10=9b+10 | | 9x+5forx=9 | | 3-x=31 | | (x*x)-x=17 | | -3f=-4f+6 | | 6+0.5t=21 | | -460=-16a+52 | | 123=5x-4(-x+6) | | -7z=7-6z | | 6+0.5t=0 | | 12X+147=7x-13-3x | | 19.50-80.00x=-780.50 | | p=s+r | | x*x-x=17 | | 2v=-v-6 | | 40x-1-60x=-6 | | -2y+6x=24 | | -2p=10-3p | | 3+4p=5p | | 64=5x-2 | | f(x-4)=2x^3-17x^2+33x | | 2k-10=3k | | 9a+5b+6a+5b= |